EVALUACION CLINICA DE RESTAURACIONES CERVICALES REALIZADAS CON UN COMPOMERO - Lahoud S., Víctor (1999)
There were select 60 dentarys pieces with caries or cervical abrassions, they divided in 2 groups: Group I 30 Teeth repared with Compómero and Group II: 30 Teeth repared with 1ónomero, that was because we want to evaluate the clinic officience during 24 months. The results shows that the restorations presented color stable, excelent integration marginal and resistence the storege and permanenay during 23 months in all cases estudies.